Kajian Etnofisika Konsep Gaya pada Permainan Tradisional Maluku: Bambu Gila - Nuryadin, Muhamad; Rumanama, Labiru; Langi, Arni Arruan (MOMENTUM : Jurnal Sosial dan Keagamaan, 2023)
Crazy Bamboo is a traditional game from Maluku Province and North Maluku Province. Some residents also call it a traditional dance. According to the belief of some residents, the bamboo was moving "raging like crazy" because it had been put into the spirit by the handler, so it had to "deploy" seven young men whose strength was to subdue it (stop it). Meanwhile, according to the author's assumption, the bamboo moves erratically due to the repulsive force, tensile force, pressing force and lifting force exerted by the player. Therefore, research was carried out to prove this assumption using student volunteers who had just studied the concept of force in physics subjects. The aim is for students to be able to think critically and scientifically about the concept of style through the crazy bamboo experiments they carry out. This research is experimental-qualitative research. The data collection technique is observing the behavior of volunteers when carrying out experiments, either directly or indirectly, namely through video recordings of the experiment. The research data were processed descriptivelyqualitatively. The results can be "concluded" that the bamboo is moving erratically "crazy" due to an environment of forces (a combination of several forces) that does not have one direction. It was also concluded that the traditional game of crazy bamboo represents the concepts of force in physics, namely: the law of inertia, the law of action-reaction, and the principle of moment of force (twisting).